2016
DOI: 10.1002/mabi.201600252
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Large‐Scale DNA Hydrogels with Excellent Blood and Cell Compatibility

Abstract: Hemocompatibility and cytocompatibility of biomaterials codetermine the success of tissue engineering applications. DNA, the natural component of our cells, is an auspicious biomaterial for the generation of designable scaffolds with tailorable characteristics. In this study, a combination of rolling circle amplification and multiprimed chain amplification is used to generate hydrogels at centimeter scale consisting solely of DNA. Using an in vitro rotation model and fresh human blood, the reaction of the hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…The activation of platelets can be determined according to ISO 10993-4 by measuring released contents from alpha granules, such as β-TG or PF4 using ELISA (Mayer et al, 2009 ; Teligui et al, 2016 ; Stoll et al, 2017 ) and detection of P-selectin (CD62P) or activated GPIIb/IIIa receptor with PAC-1 antibody using flow cytometry (Theoret et al, 2011 ; van Velzen et al, 2012 ).…”
Section: Platelet Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of platelets can be determined according to ISO 10993-4 by measuring released contents from alpha granules, such as β-TG or PF4 using ELISA (Mayer et al, 2009 ; Teligui et al, 2016 ; Stoll et al, 2017 ) and detection of P-selectin (CD62P) or activated GPIIb/IIIa receptor with PAC-1 antibody using flow cytometry (Theoret et al, 2011 ; van Velzen et al, 2012 ).…”
Section: Platelet Activationmentioning
confidence: 99%
“…The devices are divided into three categories concerning blood contact: (1) Externally communicating devices with indirect blood contact, e.g., cannulas and blood collection sets; (2) Externally communicating devices with direct blood contact, e.g., catheters and hemodialysis equipment; (3) Implant devices, e.g., heart valves, stents, and vascular grafts. So far, several studies were performed according ISO-10993-4 to evaluate various blood contacting devices and materials, such as stents (Sinn et al, 2011 ; Stang et al, 2014 ), catheters with a noble metal alloy coating (Vafa Homann et al, 2016 ), poly(2-dimethylamino-ethylmethacrylate) (PDMAEMA) (Cerda-Cristerna et al, 2011 ), and DNA hydrogels (Stoll et al, 2017 ). To perform hemocompatibility analysis, static, agitated, or shear flow in vitro models are used for the incubation of blood with the biomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…Besides by self‐assembly of proper building blocks DNA hydrogels have been formed also by rolling circle amplification (RCA), but this approach results in rather soft gels with values for the storage modulus G’ ≈ 10 Pa in the frequency range from 0.1 Hz ‐ 100 Hz . Furthermore, it has been reported that these gels comprise many differently shaped pores with sizes from 42 nm to 161 nm . Hence these gels generated by RCA form less regular structures, and are not suited to capture small guest molecules in the size of only a few nm (as typical for many enzymes).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their several attractive features, including controllable sequences, precise recognition, and low toxicity, DNA building blocks have evolved considerably in the last decades for designing advanced hydrogel systems . However, hydrogels based on spontaneous nucleotide pairing are still scarce, and the majority of reported technologies are dependent on enzymes, pH changes and temperature variations to promote DNA fragmentation . In fact, the decoration of macromolecules (e.g., polymeric chains and peptide sequences) with complementary nucleotide sequences has rendered the most effective and stimulus‐free cell‐compatible self‐assembling of hydrogel micro‐ and macroscopic units .…”
Section: Cell–biomaterials Assembliesmentioning
confidence: 99%